Quality of Life and Associated Factors among Individuals with Substance Use Enrolled in Rehabilitation Centers of Biratnagar Metropolitan City of Nepal - Karn, Rajiv Ranjan; Acharya, Yunika; Bhattarai, Ajaya (Nepal Medical College Journal, 2025)
Substance use has a negative impact on individuals physical, mental, and social well-being. However, limited research has been conducted to assess the quality of life (QoL) of individuals with substance use in eastern Nepal. This study aimed to assess the quality of life and its associated factors among individuals with substance users residing in rehabilitation centers in Biratnagar Metropolitan City, Nepal. An analytical cross-sectional study was conducted among 109 residents from seven rehabilitation centers between August 2024 and February 2025. Data were collected using sociodemographic and clinical questionnaires, and the WHOQOL-BREF tool. Multivariable linear regression was used to identify factors associated with QoL. Out of 109 respondents the mean overall quality of life score was 56.4 (22.2) with a mean score of 55.4 (19.2), 54.7 (18.8), 54.8 (23.9), and 44.3 (16.4) in physical, psychological, social, and environmental domains, respectively. After adjusting for the confounders, compared to the age group of 15- 25 years, the mean overall quality of life score was lowered by 12.7 units among 26-35 years (P= 0.04, 95% CI -25.1, 0.03), and compared to those who stay with family and friends the mean overall quality of life score was lowered by 10.9 unit among those who stay alone (P=0.01, 95% CI -19.4, -2.3). Individuals with substance use staying in rehabilitation centers generally had a moderate quality of life. However, quality of life declined with increasing age, particularly among those aged 36 to 45 and among those who lived alone highlighting the need for targeted interventions.